PENGARUH STRATEGI PEMBELAJARAN DAN KONSEP DIRI TERHADAP HASIL BELAJAR MATAKULIAH ILMU PENDIDIKAN - Gunadi, R. Andi Ahmad (Jurnal Ilmiah Widya, 2014)
Learning strategy is a fusion of a sequence of instructional activities, ways of organizing the course material and students, equipment and materials, as well as the time spent in the learning process to achieve predetermined goals. The research objective was to determine the effect of learning strategies and self-concept on learning outcomes of students in Science Education course. Research using experimental methods with a 2x2 factorial design, conducted at the University of Muhammadiyah Jakarta with samples of 44 students. The results: (1) the results of student learning with cooperative learning strategies is higher than the learning outcomes of students with expository instructional strategies; (2) the learning outcomes of students with high self-concept with cooperative learning strategies is higher than the learning outcomes of students with expository instructional strategies; (3) learning outcomes of students with low self-concept with cooperative learning strategies result is lower than the learning outcomes of students with expository learning strategies; (4) there is an interaction between learning strategies and self-concept in student learning outcomes Education courses.